2018
DOI: 10.3390/app9010053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trace Yttrium Addition and Heat Treatment on the Microstructure and Mechanical Properties of As-Cast ADC12 Aluminum Alloy

Abstract: The effects of rare earth yttrium (Y) additions and the heat treatment process on the microstructure and mechanical properties of as-cast ADC12 aluminum alloy have been investigated. The results showed that the primary Si crystals were significantly refined from long axis to fibrous or granular when the Y content was 0.2 wt%. Compared to the matrix, the mean area and aspect ratio were decreased by 92% and 75%, respectively. Moreover, the Si and Fe-rich phases were spheroidized and refined with a small average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…It is well known that the atomic radius of Y and Al are 0.182 and 0.147 nm, respectively, and the difference between Y and Al atomic radius is above 15% [34]. As a result, the Y atoms are difficult to enter the crystal lattice of the α-Al, instead, they tend to concentrate at the front of the solid-liquid interface, causing significant constitutional undercooling [35]. This will restrict the growth of α-Al and refine its dendritic grains.…”
Section: Grain Refinement By Adding Different Contents Of Al-3sr-8ymentioning
confidence: 99%
“…It is well known that the atomic radius of Y and Al are 0.182 and 0.147 nm, respectively, and the difference between Y and Al atomic radius is above 15% [34]. As a result, the Y atoms are difficult to enter the crystal lattice of the α-Al, instead, they tend to concentrate at the front of the solid-liquid interface, causing significant constitutional undercooling [35]. This will restrict the growth of α-Al and refine its dendritic grains.…”
Section: Grain Refinement By Adding Different Contents Of Al-3sr-8ymentioning
confidence: 99%
“…The mechanical and toughness characteristics of the parent alloy may be enhanced by the Y addition. Additionally, this may facilitate the processing of the alloy and increase its resistance to oxidation under high temperatures [ 12 , 13 , 14 , 15 , 16 ]. Despite its abundance among rare earth elements, Y has received little attention.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Y also exhibited a powerful modification effect on eutectic Si. Liu et al [ 16 ] reported that 0.2 wt.% Y could transform the morphology of Si phase from stripe to short fibrous or even granular. It also refined the α-Al grains and β-Al 5 FeSi phase at the same time.…”
Section: Introductionmentioning
confidence: 99%